Delayed Suprachoroidal Hemorrhage following Nd:YAG Laser Goniopuncture: A Case Report. Issue 4 (July 2015) - Rabiolo, Alessandro; Bettin, Paolo; Fiori, Marina; Ciampi, Carlo; Di Matteo, Federico; Bandello, Francesco M.
Purpose: To report a delayed suprachoroidal hemorrhage following Nd:YAG laser goniopuncture (LGP) in an eye with a previous deep sclerectomy. Methods: Case report. Results: A 75-year-old woman with advanced primary open-angle glaucoma underwent LGP due to unsatisfactory intraocular pressure (IOP) in her left eye, 1 month after undergoing deep sclerectomy in the same eye. Delayed suprachoroidal hemorrhage occurred the day after LGP execution. Conclusions: Nd:YAG laser goniopuncture is often performed to enhance IOP control following deep sclerectomy. Although LGP is usually effective and safe, severe complications, such as delayed suprachoroidal hemorrhage, may occur after its execution.